Quinary prevention in diabetes care: Need for multidisciplinary approach - D. Dutta; V. Arora; A. Dhingra; A.K. Das; Md Fariduddin; K. Shaikh; G. Priya; P. Shah; A.A. Rehim; M. John; S. Shaikh; A. Orabi; et al. (Elsevier, 2021)
Problem considered: Type 2 diabetes mellitus (T2DM) is a global pandemic with increasing prevalence worldwide. Hearsay, or reported speech, is an important contributor to diabetes care related behavior and may influence the outcomes of diabetes treatment. An emerging concept in preventive medicine is Quinary prevention which aims at preventing health-related hearsay or misinformation. Methods: A group of international clinical experts comprising endocrinologists, diabetologists, cardiologists and community medicine specialists gathered in India and discussed ways to restrain the menace of de-hearsay in diabetes care. Results: Based on the discussion, the expert panel endorsed the term 'quinary prevention,' which is a mode of preventing the spread of false health information. The panel also outlined several means through which the physician community can prevent the spread of misinformation. Conclusions: Considering the increasing use of technology by the general population, treating health care professionals should keep updating with the newer research evidences in their fields and disseminate authentic knowledge on diabetes care on social media, print media as well as other mass media, thereby diabetes promoting self-management, as well as public health.